Structural and functional characterisation of interleukin 8 haplotypes in cattle - Stojkovic, Bojan (Trinity College (Dublin, Ireland). Department of Immunology, 2016)
Accumulation of leukocytes in the tissue is one of the hallmarks of inflammation. In bovine mastitis and uterine disease neutrophils are rapidly recruited to either the mammary gland or the uterus. This leads to an increase in the number of somatic cells in milk as well as uterine tissue damage and infertility problems, both of which constitute massive constraints to global agriculture. Interleukin 8 (IL8) is a chemokine specifically involved in neutrophil recruitment and activation of anti-microbial function. It is secreted by a range of cell types including monocytes, epithelial and endothelial cells, as well as neutrophils. IL8 plays a major role in the immunopathology of mastitis and uterine disease and genetic polymorphisms within IL8 have been associated with susceptibility to a number of infectious diseases in both humans and cattle. Previously, analysis by our group, of a 2.1 kilobase spanning the upstream region of the IL8 gene transcription start site, uncovered 29 novel polymorphisms in the promoter region ofIL8, which segregate into two distinct blocks, namely IL8 haplotype 1 and IL8 haplotype 2. The aim of this project was to characterize the population genetic variation present at the IL8 gene, in a range of cattle breeds from both dairy and beef production systems, as well as to test an association between the IL8 haplotype and both somatic cell count and calving interval, traits of great agricultural importance for the Irish dairy sector.
Keywords: Biochemistry and Immunology, Ph.D.; PhD Trinity College Dublin, 2016